IoT Implementation for Development of Remote Laboratory (Case Study on Microscope Practice) - Jaja Kustija; Novall Dwi Jayanto (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2022)
During the pandemic situation, laboratories with a limited number of equipment cannot be used to their full capacity to avoid over crowded. Thus, innovation is needed in the design and arrangement of laboratories so that they can be accessed remotely with flexible schedule. However, when the community service team studied cases of teaching and learning practices during the pandemic, problems were found, among others, the imbalance between the number of tools and users, as well as limited practical opportunities in online-based learning. Therefore, in this community service a remote laboratory which could be accessed from where the users were as long as they connected to the internet was designed to provide solution to the problems. The designed remote laboratory utilized the Internet of Things (IoT) to help students do practicum on the topic Microspcope by using a remote desktop employing TeamViewer technique as a tool to access the lab computers with the users’ device. As expected, it is proven that remote laboratory can be used to overcome the imbalance between the number of laboratory equipment and laboratory users, and to avoid dangerous crowds during the pandemic as it can be accessed from where the users are located as long as they are connected to the internet.